THE IMPLEMENTATION OF AUTONOMOUS REGION IN MUSLIM MINDANAO (ARMM) PROGRAMS AND PROJECTS FOR MORO NATIONAL LIBERATION FRONT (MNLF) COMMUNITY IN MAGUINDANAO PROVINCE - Mayasa, Samsiya; Manalasal, Abdulmanan; Fiesta, Margie; Butuan, Omar (Advances in Social Sciences Research Journal, 2021)
This study aims to determine the ARMM programs and projects implementation to MNLF identified communities in the province of Maguindanao during the year periods of 2013 to 2017. Specifically, this study attempts to determine the programs and projects of ARMM to MNLF identified communities; how the implementing offices and agencies of ARMM implement these programs and projects to the MNLF-respondents; the extent of benefits do MNLF respondents have obtained from these programs and projects in terms of: (a) Livelihood (b) Health and (c) education; the problems encountered by the MNLF-respondents during the implementation of these programs and projects; and the prepared alternatives/solutions to these problems. This study further used the combination of “Quantitative and Qualitative” analysis of data. The respondents were the MNLF-Field Commanders and identified MNLF community leaders in Maguindanao Province. The Purposive Sampling was used because only One Hundred Fifty-Six (156) MNLF Commanders and Leaders under Prof. Nur Misuari were used as sample respondents. The findings show that there are serious problems that need to be addressed by the national government on the implementation of the MOU signed by the OIC-GPh-MNLF tripartite process structure to monitor the implementation of the 1996 Peace Agreement and the security, governance, economic activities, including the delivery of social services in the conflict-affected areas. Thus, the government specially, ARMM is tasked to formulate and oversee programs and projects implementation in the cities, provinces and municipalities to improve the lives of the Moros and MNLF combatants regardless of race, tribes and group or faction organization affiliation. Hence as concluded further, various socio-economic activities of the ARMM government found out failed or maybe failed again. Keywords: Implementation, Autonomous Region in Muslim Mindanao (ARMM), Programs and Projects, Moro National Liberation Front (MNLF), Maguindanao Province